2013
DOI: 10.1002/jgra.50561
|View full text |Cite
|
Sign up to set email alerts
|

The anomalous ionosphere between solar cycles 23 and 24

Abstract: [1] The solar minimum period during [2008][2009] was characterized by lower thermospheric density than the previous solar minimum and lower than any previously measured. Recent work used the NCAR Thermosphere-Ionosphere-Electrodynamics General Circulation Model to show that the primary cause of density changes from 1996 to 2008 was a small reduction in solar extreme ultraviolet (EUV) irradiance, causing a decrease in thermospheric temperature and hence a contracted thermosphere. There are similar effects in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
95
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 78 publications
12
95
0
Order By: Relevance
“…There is much evidence that indicates that Earth's thermosphere was much colder and lower in density than expected by previous minima (e.g. Solomon et al, 2010Solomon et al, , 2011Solomon et al, , 2013. This is also confirmed in the case of Mars.…”
Section: Discussion: Earth Ionosphere Comparisonsupporting
confidence: 51%
“…There is much evidence that indicates that Earth's thermosphere was much colder and lower in density than expected by previous minima (e.g. Solomon et al, 2010Solomon et al, , 2011Solomon et al, , 2013. This is also confirmed in the case of Mars.…”
Section: Discussion: Earth Ionosphere Comparisonsupporting
confidence: 51%
“…8), we can clearly see the response of the flux of particles to the evolution of the thermospheric density. Thermospheric density is directly correlated with the Sun's activity, as a result of heating driven by solar radiation, showing the same time evolution as the solar cycle (Solomon et al, 2013). Density increase at high altitude as the atmosphere expands during solar maxima leads to more frequent collisions between the trapped energetic protons and atmospheric atoms.…”
Section: The First Mode: Modulation Of the Global Flux Of Trapped Promentioning
confidence: 94%
“…Gledhill, 1976;Selesnick et al, 2014). The neutral atmosphere expands during the ascending phase of the solar cycle and, at altitudes above 100 km, its density increases (Solomon et al, 2013). As a result, in regions where mirror points are low enough, protons are removed from the inner belt through nuclear collisions with atmospheric neutral particles (Gledhill, 1976), explaining why the particle flux in the SAA region is anti-correlated with the solar activity as measured by the 10.7 cm radio flux of the Sun (Fürst et al, 2009;Casadio and Arino, 2011;Qin et al, 2014).…”
Section: Introduction: the Particle Flux In The South Atlantic Anomalymentioning
confidence: 99%
“…Many interesting observations of the sun and near-earth environment have been reported during this solar minimum (McComas et al 2008;De Toma et al 2010;Echer et al 2012;Solomon et al 2013;Fröhlich 2013;Hajra et al 2014). Haigh et al (2010) found that during the declining phase of solar cycle 23, there was a four to six times larger decline in ultraviolet emissions.…”
Section: Introductionmentioning
confidence: 95%